1996
DOI: 10.1023/a:1016057830271
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The rejection of the cells depends on cytolysis and generates potent and long lasting antitumor immunity. These data suggest that tumor cells transfected with the MIP-1 alpha gene might be useful as an effective therapy for the treatment of certain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“… 43 CCL3 is a candidate for gene therapy, because its heterologous expression can enhance antitumor immune responses. 44 , 45 Recently, melanoma WNT/β-catenin signaling was shown to prevent antitumor immunity and CCL3 and CCL4 expression were repressed by high β-catenin expression. 46 Even though we did not see effects on CCL4 production by oncogenic CARMA1 in the absence of β-catenin, these data point out that β-catenin is able to repress the expression of chemokines that promote T-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“… 43 CCL3 is a candidate for gene therapy, because its heterologous expression can enhance antitumor immune responses. 44 , 45 Recently, melanoma WNT/β-catenin signaling was shown to prevent antitumor immunity and CCL3 and CCL4 expression were repressed by high β-catenin expression. 46 Even though we did not see effects on CCL4 production by oncogenic CARMA1 in the absence of β-catenin, these data point out that β-catenin is able to repress the expression of chemokines that promote T-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…When IL-8 is transfected in cancer cells, both tumor inhibition [152, 153] and promotion [126, 154] have been observed in vivo depending on the cell type [155]. …”
Section: Clinical Significancementioning
confidence: 99%
“…When IL-8 is transfected in cancer cells, both tumor inhibition (Nakashima et al, 1996;Lee et al, 2000) and promotion (Luca et al, 1997;Inoue et al, 2000) have been observed in vivo, depending on the cell type.…”
Section: --------------------------------------------------------"mentioning
confidence: 99%